Survey on Phthalates in Beer Packaged in Aluminum Cans, PET and Glass Bottles - Kristina Habschied; Brankica Kartalović; Dušan Lazić; Vinko Krstanović; Krešimir Mastanjević (Fermentation, 2023)
Phthalates are known as endocrine disruptors and are common in plastic polymers, varnishes, and printing inks. However, they most often enter the human body through food. Plastic materials that hold food contain different chemicals, and phthalates are one of them. Phthalates can also be found in microplastics since microplastic particles serve as a vector for different chemicals that can be slowly released into food and beverages. The aim of this preliminary study was to determine the concentration and types of phthalates (dimethyl phthalate, diethyl phthalate, diisobutyl phthalate, dibutyl phthalate, bis (2-ethylhexyl) phthalate, di-n-octyl-phthalate) in beer packaged in aluminum cans, PET, and glass bottles. Ten aluminum-canned beers, sixteen PET-packaged, and eighteen glass-bottled beers were bought at a local food store and subjected to GC–MS analysis to quantify and qualify phthalates. The results indicate that PET-packaged beers can contain significant amounts of phthalates; in sample P10, the total sum of phthalates reached 219.82 µg/L. Especially high concentrations of dibutyl phthalate were found in all samples, but the highest concentration was detected in sample P13 at 92.17 µg/L. However, canned beers showed even higher levels of certain phthalates, such as bis (2-ethylhexyl) phthalate, which amounted to 326.81 µg/L in sample C1. In short, phthalates pose a serious health-concerning problem and should be regarded as such.